Migrant worker house - Dorothea Lange-Taylor:::Creator::::::::::::
A newly built windowless house in one of four quickly growing communities on the outskirts of town. These were built for agricultural workers who were on and off relief. The 45ft. by 120ft. lots sold for $400.00 ($12.00 down payment, $6.00/month @ 7% interest).